Diagnosis and Treatment of Tick-Borne Diseases in Horses - Rizzo, Toni (MD Conference Express, 2014)
Clinical recognition of tick-borne diseases can be a challenge, because tick—horse interactions are not as well studied as tick interactions with humans and dogs. In addition, clinical signs of equine tick-borne diseases are nonspecific. This article discusses tick identification, characteristics of equine tick-borne diseases, and strategies for prevention and tick avoidance.